Sarcopenia in head and neck cancer: A scoping review. - Nedeljko Jovanovic; Tricia Chinnery; Sarah A Mattonen; David A Palma; Philip C Doyle; Julie A Theurer (PLoS ONE)
Objectives In those undergoing treatment for head and neck cancer (HNC), sarcopenia is a strong prognostic factor for outcomes and mortality. This review identified working definitions and methods used to objectively assess sarcopenia in HNC. Method The scoping review was performed in accordance with Arksey and O'Malley's five-stage methodology and the Joanna Briggs Institute guidelines. Information sources Eligible studies were identified using MEDLINE, Embase, Scopus, Cochrane Library, and CINAHL databases. Study selection Inclusion criteria represented studies of adult HNC patients in which sarcopenia was listed as an outcome, full-text articles written in English, and empirical research studies with a quantitative design. Data extraction Eligible studies were assessed using a proprietary data extraction form. General information, article details and characteristics, and details related to the concept of the scoping review were extracted in an iterative process. Results Seventy-six studies published internationally from 2016 to 2021 on sarcopenia in HNC were included. The majority were retrospective (n = 56; 74%) and the prevalence of sarcopenia ranged from 3.8% to 78.7%. Approximately two-thirds of studies used computed tomography (CT) to assess sarcopenia. Skeletal muscle index (SMI) at the third lumbar vertebra (L3) (n = 53; 70%) was the most prevalent metric used to identify sarcopenia, followed by SMI at the third cervical vertebra (C3) (n = 4; 5%). Conclusions Currently, the most effective strategy to assess sarcopenia in HNC depends on several factors, including access to resources, patient and treatment characteristics, and the prognostic significance of outcomes used to represent sarcopenia. Skeletal muscle mass (SMM) measured at C3 may represent a practical, precise, and cost-effective biomarker for the detection of sarcopenia. However, combining SMM measurements at C3 with other sarcopenic parameters-including muscle strength and physical performance-may provide a more accurate risk profile for sarcopenia assessment and allow for a greater understanding of this condition in HNC.